2007
DOI: 10.1007/s10709-007-9144-7
|View full text |Cite
|
Sign up to set email alerts
|

Landscape conservation genetics of Dipteryx alata (“baru” tree: Fabaceae) from Cerrado region of central Brazil

Abstract: In this paper random amplified polymorphic DNA (RAPD) was used to evaluate the degree of among-population differentiation and associated spatial patterns of genetic divergence for Dipteryx alata Vogel populations from Cerrado region of central Brazil, furnishing support for future programs of conservation of this species. We analyzed patterns of genetic and spatial population structure using 45 RAPD loci scored for 309 trees, sampled from five different regions with two populations each. Genetic structure anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
2
11

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 59 publications
3
21
2
11
Order By: Relevance
“…Fine-scale genetic structure showed that D. alata has smaller neighborhood size and stronger spatial structure than other Cerrado tree species (Collevatti et al, 2010). Besides, Soares et al (2008) reported, using RAPD markers, a high genetic differentiation (f ST ¼ 0.15) and discontinuity among 10 populations of D. alata, from the 25 analyzed in the present study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Fine-scale genetic structure showed that D. alata has smaller neighborhood size and stronger spatial structure than other Cerrado tree species (Collevatti et al, 2010). Besides, Soares et al (2008) reported, using RAPD markers, a high genetic differentiation (f ST ¼ 0.15) and discontinuity among 10 populations of D. alata, from the 25 analyzed in the present study.…”
Section: Discussionsupporting
confidence: 55%
“…The effects of forest fragmentation on genetic diversity in Neotropical tree species in a broad geographical context have been reported recently (for example, Lowe et al, 2005;Soares et al, 2008;Moreira et al, 2009). However, because anthropogenic fragmentation is generally a recent event in evolutionary time and when considering the life cycle of these species, genetic effects of habitat fragmentation may be still undetectable (Collevatti et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The geographical coordinates available for the locations of Dipteryx alata were obtained from the literature (e.g., Soares et al, 2008), field sampling and online databases at the Centro de Referência em Informação Ambiental (CRIA: http://www.cria.org.br/). We accumulated a total of 448 geographically unique occurrence points, representing the most complete database for the geographic distribution of this species (Figure 1).…”
Section: Datamentioning
confidence: 99%
“…In the last decade, several studies have evaluated the genetic structure in Cerrado plant species (Zucchi et al, 2003;Soares et al, 2008;Moreno et al, 2009;Collevatti et al, 2001Collevatti et al, , 2010Telles et al, 2003Telles et al, , 2010Tarazi et al, 2010;Martins et al, 2006Martins et al, , 2011Moura et al, 2009Moura et al, , 2011Moraes and Sebbenn, 2011). Most of them addressed the genetic diversity and population differentiation, aiming to determine the conservation status of natural populations, which would then make it possible to infer historical events related to anthropogenic disturbance, gene flow between populations and the effect of ecosystem fragmentation.…”
Section: Introductionmentioning
confidence: 99%